Standardized facial photography - Fricker John P. (Sciendo, 1982)
A method of standardizing facial photographs including a prototype design for a head stabilizer is described. The system incorporates a projected grid with bilateral illumination, so that when a photograph is taken at right angles to the projector axis, a contour photograph results. The system may be used to achieve better documentation of cases and is particularly useful in the assessment of asymmetries. The method also lends itself to computergraphics.